The Implementation of Security Council Resolutions in the European Legal Order - Mustafa T. Karayiğit (Ankara Avrupa Çalışmaları Dergisi)
The paper examines the legal status of Security Council Resolutions and limits oftheir bindingness within the European legal order. In that context, the paper analysesthe legal relationship between international legal order under the UN and the Europeanlegal order; the jurisdiction of Community Courts with regard to both Security CouncilResolutions and iınplementing Community acts; the scope and nature of Communitycompetences and interpillar structure with respect to the implementation of SecurityCouncil Resolutions; ınodifications which would be brought to the system by theConstitutional Treaty.